2015
DOI: 10.1016/j.athoracsur.2014.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Microsphere Gel Progressively Improves Global Ventricular Function, Regional Contractile Strain, and Mitral Regurgitation After Myocardial Infarction

Abstract: Background There is continued need for therapies which reverse or abate the remodeling process following myocardial infarction (MI). In this study, we evaluate the longitudinal effects of calcium hydroxyapatite microsphere gel on regional strain, global ventricular function, and mitral regurgitation (MR) in a porcine MI model. Methods Twenty five Yorkshire swine were enrolled. Five were dedicated weight-matched controls. Twenty underwent posterolateral infarction by direct ligation of the circumflex artery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Using a clinically relevant large animal model of a pig with MI and threedimensional (3D) echocardiography, the Gorman Group and collaborators have recently reported that epicardial injection of Radiesse after MI increases infarct stiffness, reduces infarct expansion, and stabilizes the LV chamber size [4,5]. By using the novel high-resolution 3D magnetic resonance imaging (MRI) imaging technique, 4D velocityencoded MRI flow analysis, and the same animal model, this well-designed and interesting study extended their previous findings by showing that epicardial injection of Radiesse significantly improves global LV function, borderzone function, and mitral regurgitation after MI [6]. This translational research strongly suggests that Radiesse could be a promising new therapy for treating MI.…”
Section: Invited Commentarysupporting
confidence: 61%
“…Using a clinically relevant large animal model of a pig with MI and threedimensional (3D) echocardiography, the Gorman Group and collaborators have recently reported that epicardial injection of Radiesse after MI increases infarct stiffness, reduces infarct expansion, and stabilizes the LV chamber size [4,5]. By using the novel high-resolution 3D magnetic resonance imaging (MRI) imaging technique, 4D velocityencoded MRI flow analysis, and the same animal model, this well-designed and interesting study extended their previous findings by showing that epicardial injection of Radiesse significantly improves global LV function, borderzone function, and mitral regurgitation after MI [6]. This translational research strongly suggests that Radiesse could be a promising new therapy for treating MI.…”
Section: Invited Commentarysupporting
confidence: 61%
“…Animals were first sedated with intramuscular ketamine injections (25–30 mg/kg), intubated, and mechanically ventilated. General anesthesia was maintained on mixed isoflurane (1.5–3.0%) and oxygen, which was delivered by volume-controlled ventilation (tidal volume 10–15 mg/kg) [28]. A posterolateral infarction was induced by ligation of the left circumflex artery (LCX) and select obtuse marginal (OM) branches.…”
Section: Methodsmentioning
confidence: 99%
“…Following infarct induction, thin MRI compatible, platinum wire markers were sutured to the epicardium to outline the infarct area. These markers were tracked for quantitative assessment of infarct expansion over time (Figure 2A) [28]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations